(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The Shokaido Dojo in Bungo Regency is one of the karate training centers located in Bungo Regency. During an interview with the coach, it was revealed that this dojo had achieved unsatisfactory results in the last three years, from 2022 to 2024. Based on observations and interviews, the researcher tentatively concluded that the factor influencing this decline was interest. The purpose of this study was to determine the level of interest in karate training at the Shokaido Dojo in Bungo Regency. This study used a descriptive method with a quantitative approach to describe the level of interest in karate training at the Shokaido Dojo in Bungo Regency. The population in this study consisted of 20 people. Based on the results obtained, the intrinsic indicator results were in the very good category, namely 4 people (20%). In the good category, there were 11 people (25%), and in the moderate category, there were 5 people (25%). The results of the extrinsic indicators were in the good category, with 13 people (65%). In the moderate category, there were 5 people (25%), and in the low category, there were 2 people (10%). Based on the results obtained, it can be concluded that the athletes’ interest in participating in Shokaido Karate training in Bungo Regency is in the good category with an average score of 87.6, which is in the interval range of 82.5 ≤ 97.5.